(untitled) (Research, Society and Development, 2019)
The present work is immersed in the context of the changes brought about by the insertion and growth of games in society - especially in the field of education - where two important practices complement each other: the hermeneutic game and gamification. Thus, we have as a general objective to relate hermeneutic practice to gamification, specifying in the main concepts related to these models, as well as their phenomena and teaching strategies, taking into account traditional methodologies and the influence of new technologies and media on the formation of the individual. As a conclusion after conducting an exploratory research, it is noted how every day new issues related to the theme of the game with the learning function or teaching method appear, a factor that points to a future of teaching more and more gamificado and dynamic.